A study on the marketing practices adopted by small and medium enterprises of automotive industry in Malaysia / Hazliza Haron and Ina Murni Hashim - Haron, Hazliza; Hashim, Ina Murni (2005)
This study tries to investigate the marketing practices adopted by SMEs of automotive industry in Malaysia. The scope of this study is focused on automotive industry because it is one of the industries in the country that are developing rapidly. This is especially emphasized when the global market is talking about AFTA which is nearing us soon. Specifically, the objective of this study is to look at the way SMEs of automotive industry perform their marketing practices. Besides that, factors involved in their formulation of marketing strategies were also identified. Primary data were the main instrument used to collect data with regards to the purpose of this research. From the total population, the researchers had managed to collect about 10% as their sample. The response rate was a bit small, but it is expected to indicate the marketing practices performed by the SMEs. A simple frequency analysis was used to analyze those data in order to answer the objectives. It can be said that the marketing practices adopted by these SMEs are rather moderate. Most of the products offered were purely tangible products and they brand them under manufacturer's brand As for pricing element, the companies aim towards getting return on their investment. They do practice credit sale with a 2 months of payment period Most of the companies distribute their products direct to their users. This is because according to them, cost is the main factor that influenced their distribution decision. The companies prefer to display their products as their way of attracting customers to buy their products. Since their products are tangible products and cost is a factor to these companies, display is probably a cheaper and quicker way to attract customers. Of all the promotional method available that are personal selling, sales promotion, advertising and public relation, these SMEs mostly adopted personal selling as their main promotional method. There were 7 sub variables that this research had focused on. This is because those variables are considered as the most important variables used to develop a company's product strategy. Those sub variables are product quality, product features, product variety, product style/design, product brand name, product packaging and product services and warranty. Among the seven variables, it is found out that quality is considered as the most important factor in developing product strategy. This is followed by product features and product services and warranty. For pricing element, majority of the SMEs of automotive industry are using cost-plus pricing as their based in determining price for their products. This is probably because their main pricing objective is to get return on their sales.